PEMBINAAN CLCK (CONTOH, LATIHAN, CONTROL, KERJA MANDIRI) DALAM PROGRAM KERJA GURU UNTUK MENINGKATKAN KOMPETENSI GURU DI SDN 091621 PERDAGANGAN - Benni Marsal (JURNAL TEMATIK, 2020)
The purpose of this study is to find out the CLCK Development model in teacher work programs that can improve Teacher Competence at SDN 091621 Trade. This type of research is a school action research consisting of 2 cycles. Each cycle consists of 4 stages, namely the planning, action, observation and reflection stages. Based on the results of the discussion it can be concluded that the average score from the observation of the pre-cycle of competence in carrying out learning is 70.92 or with sufficient quality and the average score of observations in cycle 1 about the competence of implementing learning is 87.54 or good quality level. Increasing the results of the average score of pre-cycle data, cycle 1 and cycle 2 is as follows: the results of the cycle 1 score is higher than the pre-cycle data score of 16.62, the results of the cycle 2 score are higher than the score of cycle 1 that is equal to 10.15, the results of the data score II are higher than the pre-cycle data score of 26.77, from 10 teachers after being supervised twice there is an increase in the ability of teachers to increase competence in implementing excellent learning.